Is catheterization via distal transradial access feasible in children? From vessel diameter perspective - Zhao, Yidong; Chen, Tao; Yang, Ling; Mao, Wenjie; Wan, Yu; Zhang, Liwen; Ding, Heng; Cai, Gaojun; Huang, Zhiying (Frontiers in Cardiovascular Medicine, 2024)
Background Distal radial artery (DRA) access is an infrequent alternative access for pediatric catheterization. The feasibility of using the DRA for arterial catheterization in children depends on the vessel's size. Objectives This study aims to provide a reference for pediatric catheterization via DRA access by evaluating the diameter of the DRA in the anatomic snuffbox (AS). Methods We conducted a retrospective review of clinical and vascular ultrasound data of 412 children (ages 3–12) who were scheduled for arterial blood gas analysis via the DRA due to serious respiratory diseases between June 2023 and October 2023. Results The corrected DRA diameter in the AS was 1.97 ± 0.37 mm overall, with no significant difference between males (1.98 ± 0.38 mm) and females (1.95 ± 0.35 mm) (p = 0.457). The anteroposterior, transverse, and corrected DRA diameters increased significantly with age (p < 0.05). The DRA diameter was significantly smaller than the proximal radial artery (PRA) diameter (1.97 ± 0.37 mm vs. 2.05 ± 0.33 mm, p < 0.001) but larger than the ulnar artery (UA) diameter (1.97 ± 0.37 mm vs. 1.88 ± 0.33 mm, p < 0.001). The proportions of patients with a DRA diameter greater than 2.0 mm and 1.5 mm were 38.83% and 86.89%, respectively. The proportions of patients with DRA diameters >2.0 mm and >1.5 mm increased significantly with age (p < 0.01). The percentages of individuals with a DRA/PRA ratio ≥1.0 were 55.10% overall, 52.12% in males, and 58.60% in females. DRA diameter showed significant correlations with age (r = 0.275, p < 0.01), height (r = 0.319, p < 0.01), weight (r = 0.319, p < 0.01), BMI (r = 0.241, p < 0.01), wrist circumference (r = 0.354, p < 0.01), PRA diameter (r = 0.521, p < 0.01), and UA diameter (r = 0.272, p < 0.01). Conclusion The DRA diameter in children increases with age and size, making cardiac catheterization is theoretically feasible. Preoperative evaluation of the vessel diameter and intraoperative ultrasound-guided intervention are recommended for paediatric catheterization via the DRA access.